2018
DOI: 10.1111/jeb.13254
|View full text |Cite
|
Sign up to set email alerts
|

Flexible parents: joint effects of handicapping and brood size manipulation on female parental care inNicrophorus vespilloides

Abstract: Parental care is highly variable, reflecting that parents make flexible decisions in response to variation in the cost of care to themselves and the benefit to their offspring. Much of the evidence that parents respond to such variation derives from handicapping and brood size manipulations, the separate effects of which are well understood. However, little is known about their joint effects. Here, we fill this gap by conducting a joint handicapping and brood size manipulation in the burying beetle Nicrophorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 50 publications
6
38
0
Order By: Relevance
“…Evidence from studies on N. vespilloides also suggests that parents respond to cues other than begging when determining the amount of provisioning, as the parents provision more food to inbred offspring, although the same offspring also beg less than their outbred counterparts (Mattey, Richardson, Ratz, & Smiseth, 2018). Similarly, adult N. vespilloides are known to adjust their behaviour to the number of larvae in a brood (Ratz & Smiseth, 2018; Smiseth & Moore, 2007). In our study, the older larvae of the mid‐aged and old treatments may have been assessed as being of good quality, potentially due to their size or associated traits, thereby prompting the female into elevating the amount of care beyond the level provided by control females.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies on N. vespilloides also suggests that parents respond to cues other than begging when determining the amount of provisioning, as the parents provision more food to inbred offspring, although the same offspring also beg less than their outbred counterparts (Mattey, Richardson, Ratz, & Smiseth, 2018). Similarly, adult N. vespilloides are known to adjust their behaviour to the number of larvae in a brood (Ratz & Smiseth, 2018; Smiseth & Moore, 2007). In our study, the older larvae of the mid‐aged and old treatments may have been assessed as being of good quality, potentially due to their size or associated traits, thereby prompting the female into elevating the amount of care beyond the level provided by control females.…”
Section: Discussionmentioning
confidence: 99%
“…Female burying beetles will sometimes adjust provisioning in response to mate removal (Fetherston et al, 1994) but sometimes do not (Rauter & Moore, 2004;Smiseth et al, 2005). More recently, handicapping by the attachment of lead weights to one parent has been used to study negotiation (Suzuki & Nagano, 2009;Creighton et al, 2015;Suzuki, 2016;Ratz & Smiseth, 2018). Other studies have examined the effect of larval begging on parental provisioning.…”
Section: Introductionmentioning
confidence: 99%
“…Wright and Cuthill 1989;Harrison et al 2009), confirming that parents plastically reduce the amount of care they provide when the cost of care increases. However, a recent study on the burying beetle Nicrophorus vespilloides found that handicapped females provided more care than control females (Ratz and Smiseth 2018). This finding contradicts the implicit assumption that handicapping simply increases the cost of care.…”
Section: Introductionmentioning
confidence: 93%
“…Parental care encompasses any parental trait that enhances the survival and/or growth of a parent's offspring, often at a cost to the parent's ability to invest in other current or future offspring (Clutton-Brock 1991;Royle et al 2012). Parental care is highly variable (Clutton-Brock 1991;Royle et al 2012), reflecting that parents make flexible decisions about how much care to provide due to variation in the cost of care to themselves and/or the benefit to their offspring (Royle et al 2014;Ratz and Smiseth 2018). For example, parents are expected to provide less care should there be an increase in the cost of care, as shown by handicapping experiments on birds and insects (Wright and Cuthill 1989;Harrison et al 2009;Suzuki and Nagano 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation